Trade adjustment in Asia : past experiences and lessons learned - Bacchetta, Marc (Asian Development Bank Institute and World Trade Organization, 2020)
This publication aims to provide new insights on adjustment to trade by examining both how firms and how labor markets adjust to trade. A better understanding of how firms adjust can help us understand how workers are affected by trade. Firms have different margins of adjustment, and depending on which of those margins they use in reaction to trade shocks, workers will be affected differently. The publication shows that there is much to learn from the Asian experience.